Enrichment of honey with flavour of ginger - Kumar Patel, Amit; Saran, Saty; Prakash, K.; Anandrao Laichattiwar, Mukesh; Banerjee, Adrita; M Madalageri, Deepa; Marimuthu, S.; Assaba Mohammed Shafi, Ali; Singh, Rathodlal (Journal of Neonatal Surgery, 2025)
In response to rising consumer demand for natural, health-promoting, and flavourful food products, this study investigates the development and characterization of a novel functional honey-based product: ginger honey. The aim was to evaluate the effects of ginger incorporation on the sensory attributes, physicochemical properties, antioxidant capacity, and antibacterial activity of honey. Sensory evaluation revealed that the addition of ginger introduced woody and fresh notes, along with increased astringency and bitterness, while decreasing sweetness, floral aroma, fruity notes, and overall acceptability. Physicochemical analyses indicated that ginger significantly increased colour intensity, moisture content, water activity, electrical conductivity, pH, and reducing sugar content, while reducing the total sugar content. Antioxidant capacity, measured through total phenolic content, iron chelating ability, superoxide anion, and hydroxyl radical scavenging activities, was notably enhanced due to ginger's bioactive constituents such as gingerol and phenolic compounds. Antibacterial testing using agar well diffusion assay showed increased inhibitory effects of ginger honey against Enterococcus faecalis, suggesting synergism between honey and ginger components. However, no significant antibacterial enhancement was observed against Pseudomonas aeruginosa. While ginger fortification enhanced the functional qualities of honey, it negatively impacted sensory acceptability. This trade-off highlights the need for formulation optimization to balance health benefits with consumer preferences. The study supports ginger honey’s potential as a value-added functional food with enriched antioxidant and antimicrobial properties.